High- and Low-Ti tholeiites in the Eastern Parnaíba Basin: Regional correlations with Mesozoic large igneous provinces - Cícera Neysi de Almeida; Julio Cezar Mendes; Sérgio de Castro Valente; Francisco de Assis Negri; Alan Miranda; Artur Corval Vieira; Sílvia Regina de Medeiros; Leonardo Borghi; Pedro Miloski; Mayara Cardoso; Juliana Godot (Brazilian Journal of Geology)
Abstract Two tholeiitic magmatic events are recorded at the Eastern Border of the Parnaíba Basin comprising the Jurassic Mosquito Formation and the Cretaceous Sardinha Formation. They are chronocorrelated to the Central Atlantic Magmatic Province Large Igneous Province (CAMP LIP) and Equatorial Atlantic Magmatic Province (EQUAMP LIP), respectively. The latter is also chronocorrelated with the Paraná-Etendeka Province (PEMP LIP). Five groups of tholeiitic rocks are representative of magmatic episodes with different ages and tectono-magmatic context: Low-Ti Group I, High-Ti Group IIa, High-Ti Group IIb, High-Ti Group III, and High-Ti Group IV. The geochemical data of Groups I, IIa, and IIb are similar to those of tholeiitic basalts from Jurassic CAMP LIP, whereas rocks in Groups III and IV can be related to the Cretaceous EQUAMP LIP as well as High-Ti basalts of the PEMP LIP. The chemical differences between the two magmatic events indicate changes in the mantle composition underlying to the Parnaíba Basin over geological time. It is likely that the Brasiliano-Pan African orogenies, which preceded Jurassic rifting, affected the mantle sources of the Groups I and II magmas. Conversely, the composition of the mantle underlying the Parnaíba Basin was modified by the impingement of a mantle plume during the Cretaceous.